Self-defining memories in non-justice and justice-involved individuals: possible relations to recidivism - Elias, Hannah; Krackow, Elisa (Frontiers in Psychology, 2023)
Given the high rates of recidivism in adults, additional efforts in this area are warranted. In this paper, we provide a developmental perspective on self-defining memories, a specific type of autobiographical memory. We review the literature on self-defining memories in offenders and non-offenders high in psychopathic traits. Next, we present an empirically based conceptual framework regarding self-defining memories and recidivism, including a model of recidivism that integrates self-defining memories with identity, decision making, and behavioral processes related to recidivism. We then critique this model. We call for future research to test this model. Should results be fruitful, we discuss potential applications of this work.